Biological factors of birth and overweight in adolescents: exploring metabolic imprinting (Research, Society and Development, 2020)
Cross-sectional study with a quantitative approach, carried out in two municipal schools in Campina Grande-PB, with schoolchildren aged 10 to 16 years 11 months and 29 days, with overweight or obesity. Data were collected through a questionnaire and anthropometric measurements between May and August 2018. The sample selection was conglomerated and stratified by school size, with the final sample consisting of 71 students. Those with motor, cognitive and pulmonary limitations were excluded; presence of genetic syndrome; conducting weight loss treatment; use of drugs that alter the metabolism; postpartum condition, pregnancy or lactation. For data analysis, the program SPSS - version 22.0 was used, considering the level of statistical significance of 5%. Of the 71 schoolchildren evaluated, the average age was 12.7 years, mostly overweight, most of them female for overweight (PE) as a whole, and obesity for boys. In addition, it was observed that the majority did not perform the recommended AME for at least six months, and most were born with weight appropriate for gestational age. Despite the fact that most of the related variables do not present statistical significance among PE, understanding this dynamic among these biological factors at birth is a primary task in order to complement the picture of components associated with the increase in PE. Thus, with a view to prevention, it is important to investigate the biological factors of birth in order to understand and provide subsidies to intervene in the environment, avoiding the occurrence of harmful effects on the health of infants in adulthood.